BLENDED LEARNING STRATEGIES FOR EFL STUDENTS: A COMPREHENSIVE EXPLORATION - Turdiyeva Zahro Mirsoliyevna (PEDAGOGS, 2025)
Blended learning has revolutionized educational practices by integrating traditional classroom instruction with digital technologies. This approach provides EFL (English as a Foreign Language) students with a dynamic learning environment that fosters flexibility, personalized instruction, and enhanced engagement. Originating in the late 20th century, blended learning has gained popularity due to advancements in technology and the increasing need for innovative teaching methods. This article explores the historical development of blended learning, its key contributors, reasons for adoption in EFL education, and effective strategies such as flipped classrooms, station rotation, and gamification. Furthermore, it highlights empirical studies demonstrating the positive impact of blended learning on EFL students' language acquisition, motivation, and critical thinking.